A Discussion of Obser-View as a Method of Generating Data in the Construction Industry - Nnedinma I. Umeokafor (Institute of Research and Community Outreach - Petra Christian University, 2015)
This study demonstrates the paradigmatic position of obser-view and argues for the incorporation of reflectivity in obser-view to foster rigorous data generation. Aimed at introducing obser-view to the construction industry as a method of generating data, this study critically examines obser-view, exploring its application to construction research. Obser-view is an emerging data collection technique developed by Kragelund in 2006, where a non-scripted interview immediately post-observation is conducted. This helps to gain a deeper understanding of the phenomenon. Although researchers adopt various strategies to ensure rigor in qualitative research, there are still concerns in relation to validity, reliability, bias and objectivity in qualitative research. However, developing strategies that will help in gaining a deeper understanding of the phenomenon in study and tackling the aforementioned challenges will help in ensuring transparency in qualitative research. A review of literature is presented, the limitations and benefits of obser-view are also presented.